Conceptual understanding in science learning and the role of four psychometric variables: a person-centered approach - Vaiopoulou, Julie; Tsikalas, Themistocles; Stamovlasis, Dimitrios; Papageorgiou, George (Frontiers in Psychology, 2023)
The present study investigated conceptual understanding in learning science in relation to four cognitive variables: logical thinking, field-dependence/field-independence, and divergent and convergent thinking. The participants were fifth- and sixth-grade elementary school pupils involved in different mental tasks, where they had to describe and interpret phenomena related to changes of matter. This brief report presents data from the students’ understanding of evaporation, and the method of analysis, a person-centered approach, is explicated. Latent class analysis (LCA) was applied to reveal distinct clusters of cases sharing similar patterns of responses. The use of LCA aligns with theoretical conjectures related to a stepwise conceptual change process, and the hypothetical steps correspond to the identified discrete latent classes (LCs). Subsequently, the LCs were associated with the four cognitive variables as covariates, thus providing empirical evidence for the role of the above-mentioned individual differences in children’s learning in sciences. Methodological issues and theoretical implications are discussed.